Temporal residency patterns of Risso's dolphins, Grampus griseus, off Pico Island, Azores - Hartman, Karin L. (2009)
Temporal residency patterns of Risso's dolphins, Grampus griseus, occurring off Pico Island, Azores archipelago, were studied by conducting photoidentification surveys during 25 sampling months (May 2004-January 2007). A total of 1102 dolphins was identified, of which a restricted population (n= 996) was further analyzed. Temporal residency patterns were classified using year, season and monthly presence, and defined in three groups: non resident, partial resident and resident. Risso's dolphins were present in the research area in all seasons and all years. The seasonally parameter (4 seasons sighted) resulted in the highest percentage of residents (17%, n = 173). Age-classes and sexes showed different temporal residency patterns. Residents consisted largely of adult males and sub-adults, and were present in the research area throughout the sampling period. Partial and resident females were less frequently sighted, but showed a resident pattern when calving and nursing. The presence and number of old resident females strongly decreased. A calving peak was found in summer. Together with the existence of a resident population, this indicates that Pico is functioning as a critical habitat for Risso's dolphins occurring off Pico Island, was set up in 2000 by the Nova Atlantis Foundation. The aim of the present study was to obtain information on the residency pattern of Risso’s dolphins around Pico Island.